Metabolic Acidosis in Children: A Literature Review - Syed Ahmed Zaki; Preeti Shanbag (European Medical Journal, 2023)
Metabolic acidosis is characterised by a primary decrease in the serum bicarbonate concentration, a secondary decrease in the arterial partial pressure of CO2, and a reduction in blood pH. Metabolic acidosis, acute or chronic, may have deleterious effects on cellular function and cause increased morbidity and mortality. A systematic review of the available literature was performed to identify data on the prevalence, manifestations, cause, outcomes, and treatment of metabolic acidosis in children. Online databases (Ovid Medline, Embase, and PubMed), commercial search engines (including Google), and chapters on metabolic acidosis in the standard textbooks of paediatrics and medicine were reviewed. Systematic approach to acute metabolic acidosis starts with proper history taking and examination. This is followed by assessment of acid-base parameters, including pH, partial pressure of CO2, and bicarbonate concentration in arterial blood. Blood gas is needed to differentiate primary metabolic acidosis from compensated respiratory alkalosis. Once the diagnosis of a metabolic acidosis has been confirmed, serum electrolyte values are used to determine the serum anion gap. The various causes of increased and normal anion gap metabolic acidosis have been discussed in the article. The main aim of treatment in metabolic acidosis is to reverse the primary pathophysiology. In acute metabolic acidosis, sodium bicarbonate therapy is not beneficial due to potential complications and is reserved for specific situations. Base therapy is used in chronic metabolic acidosis where it ameliorates many of its untoward effects. Other modalities of treatment of metabolic acidosis include peritoneal or haemodialysis and tris-hydroxymethyl aminomethane.